The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12991-020-00276-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of mental disorders in the nationwide primary care population in Latvia: a cross-sectional study

Abstract: Background: Mental disorders are common amongst patients in primary care. There are no published studies on the prevalence of mental disorders in primary care patients in Latvia. The purpose of the study was to evaluate the current prevalence of mental disorders in the nationwide Latvian primary care population and to study possible associated factors and comorbidity of mental disorders. Methods: A cross-sectional study within the framework of the National Research Program BIOMEDICINE 2014-2017 was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
(110 reference statements)
10
10
1
Order By: Relevance
“…The incidence of anxiety and depression in women was approximately twice that of men. The present ndings seem to be consistent with other research which has found that sex is a contributing factor in anxiety and depression [19,20]. This is also con rmed by our earlier observations [9].…”
Section: Discussionsupporting
confidence: 94%
“…The incidence of anxiety and depression in women was approximately twice that of men. The present ndings seem to be consistent with other research which has found that sex is a contributing factor in anxiety and depression [19,20]. This is also con rmed by our earlier observations [9].…”
Section: Discussionsupporting
confidence: 94%
“…The incidence of anxiety and depression in women was approximately twice that of men. The present ndings seem to be consistent with other research which has found that gender is a contributing factor in anxiety and depression [18,19]. This is also con rmed by our earlier observations [8].…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies, our results demonstrated that unemployment increases the chance of anxiety and depression [19,28,29]. Economically, unemployment status increases the risk of development and progression of psychiatric disorders and strong evidence is available in this regard for depression and anxiety disorders [30][31][32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations